2020
DOI: 10.5946/ce.2020.143
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Capsule Endoscopy and Balloon-Assisted Enteroscopy in the Optimal Management of Small Bowel Bleeding

Abstract: The small bowel had long been considered a dark unapproachable tunnel until the invention of capsule endoscopy and doubleballoon enteroscopy in the 21st century, which revolutionized the diagnosis and management of small bowel diseases, including bleeding. Various imaging modalities such as computed tomographic enterography, angiography, capsule endoscopy, and balloonassisted enteroscopy play vital roles in the diagnosis and management of small bowel bleeding. The choice of modality to use and timing of applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Second, indications for DBE are very diverse and heterogeneous. Methods for classifying indications can also vary [ 22 , 23 , 24 , 25 ], making it difficult to interpret the results. Therefore, we tried to classify reasons for the test as rationally as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Second, indications for DBE are very diverse and heterogeneous. Methods for classifying indications can also vary [ 22 , 23 , 24 , 25 ], making it difficult to interpret the results. Therefore, we tried to classify reasons for the test as rationally as possible.…”
Section: Discussionmentioning
confidence: 99%
“…VCE involves swallowing a disposable capsule with a data recorder by patients. [16][17][18] A recent meta-analysis study on VCE (328 original articles with 86,930 enrolled patients) has reported that obscure GI bleeding (n=44,750) is the most common indication for VCE during the recent two decades, followed by clinical symptoms, Crohn's disease, neoplastic lesions, and celiac disease. 19 The detection rate of VCE was 59% for all indications, and 56% for obscure GI bleeding.…”
Section: Video Capsule Endoscopymentioning
confidence: 99%